Extensible composite hole transport layer and perovskite solar cell based on same
By adopting a scalable composite hole transport layer in perovskite solar cells and combining DC sputtering and immersion methods, the problem of large-area uniform deposition of hole transport layer is solved, and cost reduction and performance improvement are achieved.
Patent Information
- Application Number
- CN202411890788.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
In existing perovskite solar cells, the preparation method of hole transport layer cannot achieve large-area uniform deposition, which limits the commercial development of devices.
A scalable composite hole transport layer consisting of the bottom nickel oxide film and the top self-assembled single molecule layer is used to achieve large-area preparation by deposition of nickel oxide film and immersion.
The uniform deposition of the hole transport layer is achieved, the preparation cost is reduced, and the performance and efficiency of perovskite solar cells are improved.
Smart Images

Figure CN119677305A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of thin-film perovskite solar cell materials and devices, and in particular to an expandable composite hole transport layer and a perovskite solar cell based thereon. Background Art
[0002] Perovskite solar cells are a new type of solar cells. Their high photoelectric conversion efficiency and low manufacturing cost make their application prospects very broad. Perovskite solar cell devices are generally prepared by stacking multiple functional layers, mainly including a transparent conductive glass layer, a hole transport layer, a perovskite light absorption layer, an electron transport layer, and a back electrode. At present, the photoelectric conversion efficiency of a single-cell laboratory small-area perovskite solar cell has quickly exceeded 26%, which is close to that of commercial crystalline silicon solar cells.
[0003] Among them, the hole transport layer is an important functional layer for hole extraction and transport in perovskite devices, which has a great influence on the photovoltaic performance of the device. The commonly used Spiro-OMeTAD hole transport material is mainly used in formal perovskite devices, but its stability is poor and it is easy to absorb moisture. Trans perovskite devices have the characteristics of low hysteresis and high stability and have attracted much attention in recent years. At present, the commonly used hole transport materials of trans structure, such as nickel oxide nanocrystals (NiO X ), self-assembled monolayer (SAM), polytriarylamine (PTAA), polyethylenedioxythiophene:polystyrenesulfonic acid (PEDOT:PSS), etc., all require solution spin coating to prepare, which is not suitable for depositing large-area hole transport layers. Therefore, in the process of perovskite solar cells moving towards industrial production, it has become a top priority to explore a scalable hole transport layer deposition strategy. Summary of the invention
[0004] Based on the above-mentioned deficiencies in the prior art, the present invention aims to provide a large-area preparation method of an expandable composite hole transport layer, so that it is compatible with the preparation of large-scale photovoltaic modules.
[0005] In order to achieve the purpose, the present invention adopts the following preparation method:
[0006] In one aspect of the present invention, the present invention provides an expandable composite hole transport layer for perovskite solar cells, wherein the expandable composite hole transport layer is a composite structure consisting of a bottom nickel oxide film and a top self-assembled monolayer.
[0007] The present invention also provides a large-area preparation method of the expandable composite hole transport layer, comprising the following steps:
[0008] (1) using a metal nickel target or a ceramic nickel oxide target to sputter and deposit an underlying nickel oxide film;
[0009] (2) annealing the nickel oxide film;
[0010] (3) depositing a top self-assembled monolayer on the nickel oxide film by an immersion method;
[0011] (4) annealing the self-assembled monolayer;
[0012] (5) cleaning the top self-assembled monolayer by immersion method;
[0013] (6) Annealing the cleaned top self-assembled monolayer to obtain the expandable composite hole transport layer.
[0014] Preferably, in step (1), the purity of the metal nickel target or the ceramic nickel oxide target is not less than 95% (by weight), the sputtering is magnetron sputtering, the sputtering power is 20W-120W, the gas pressure is 0.1Pa-10Pa, the volume ratio of chamber oxygen and argon is 1-20:0-1, and the thickness of the formed underlying nickel oxide film is 5-30nm.
[0015] Preferably, in step (2), the annealing treatment is carried out in an air environment, the annealing temperature is 25-500° C., and the annealing time is 1-60 min.
[0016] Preferably, in step (3), the immersion method is to add the monomolecular material to a solvent (preferably one or more of ethanol, isopropanol, deionized water, etc.) to prepare a monomolecular layer solution with a concentration of 0.02-0.05 mg / mL, and then immerse the sample in the monomolecular layer solution for 1-12 hours at a solution temperature of room temperature -40°C. The monomolecular material is further preferably 2-(3,6-dimethyl-9H-carbazole-9-yl)ethyl)phosphonic acid (Me-2PACz), (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid (MeO-2PACz), (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid (Me-4PACz), (2-(9H-carbazole-9-yl)ethyl)phosphonic acid (2PACz), (4-(9H-carbazole-9-yl)butyl)phosphonic acid ( ... One or more of (4-(7H-dibenzocarbazole-7-yl)butyl)phosphonic acid (4PACz), (4-(2,7-dibromo-9,9-dimethylacridin-10(9H)-yl)butyl)phosphonic acid (DMAcPA), (2-(3,6-dibromo-9H-carbazole-9-yl)ethyl)phosphonic acid (Br-2PACz) and (4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl)phosphonic acid (MeO-4PACz).
[0017] Preferably, in step (4), the annealing treatment is carried out in an air environment, the annealing temperature is 80-120° C., and the annealing time is 10-20 min.
[0018] Preferably, in step (5), the cleaning solution used for cleaning is one or more of ethanol, isopropanol and deionized water, and the immersion time in the cleaning solution is 0-120s.
[0019] Preferably, in step (6), the annealing treatment is carried out in an air environment, the annealing temperature is 80-120° C., and the annealing time is 3-5 min.
[0020] In another aspect of the present invention, an expandable composite hole transport layer-based perovskite solar cell is provided, wherein the hole transport layer of the perovskite solar cell is the above-mentioned expandable composite hole transport layer composed of a bottom nickel oxide film and a top self-assembled monolayer.
[0021] Furthermore, the expandable composite hole transport layer-based perovskite solar cell includes a transparent substrate; a transparent conductive layer is formed on the transparent substrate; the expandable composite hole transport layer is formed on the transparent conductive layer; a perovskite layer is formed on the expandable composite hole transport layer; an electron transport layer is formed on the perovskite layer; and a back electrode is formed on the electron transport layer.
[0022] Preferably, the transparent conductive layer is selected from one or more of indium tin oxide (ITO), fluorine-doped tin dioxide (FTO) and indium-doped zinc oxide (AZO).
[0023] Preferably, the component of the perovskite layer is MA x FA 1-x PbI 3 . Combine MAI, FAI, PbI 2 Dissolve in a mixed solvent of DMF:DMSO (0-5):(0-5) in a mass ratio of (0-250):(0-200):(500-800), stir at 65°C±5°C for 10-12h to obtain a perovskite precursor solution. Then, spin-coat the perovskite precursor solution on the expandable composite hole transport layer at a spin-coating speed of 3000-4000 rpm for 30-40 seconds. During the spin-coating process, ethyl acetate is used as an anti-solvent. Finally, place on a heating table at 120±5°C and dry for 15±2min to obtain MA. x FA 1-x PbI 3 Perovskite layer.
[0024] Preferably, the electron transport layer is selected from one or more of (6,6)-phenyl-C61-butylene isomethyl ester (PCBM), C60, 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline (BCP). More preferably, at 3*10 -4 Pa, vacuum evaporated C60 with a thickness of 30-80 nm at a deposition rate of 0.5-1 A° / s as an electron transport layer, and then continued to evaporate BCP with a thickness of 1-10 nm at a deposition rate of 0.5-1 A° / s as a secondary electron layer.
[0025] Preferably, the back electrode is selected from one or more of ITO, AZO, IWO, Au, Ag, Cu, Al, Ni, Cr, and Pt. More preferably, Ag with a thickness of 80-120 nm is evaporated at an evaporation rate of 1-2 A° / s as the back electrode.
[0026] Preferably, the transparent substrate is glass.
[0027] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0028] 1) Most of the existing high-performance hole transport layers are prepared based on solution spin coating, which cannot achieve uniform large-area thin film deposition, limiting the commercial development of perovskite solar cells. X The method of hole transport layer and immersion deposition of self-assembled monolayer can expand the processable size of the substrate under the premise of ensuring uniform deposition of the hole transport layer.
[0029] 2) Most common magnetron sputtering nickel oxide films use ceramic nickel oxide targets as sputtering sources and adopt radio frequency sputtering to deposit films, which greatly increases the preparation cost of the film and has low deposition efficiency. The present invention adopts direct current sputtering metal nickel targets, which can effectively increase the sputtering rate and reduce the device preparation cost.
[0030] 3) The common spin coating method for preparing self-assembled monolayers requires a relatively high concentration of precursor solution. The method of the present invention can reduce the amount of precursor powder to one tenth and achieve material recycling, greatly reducing the preparation cost of perovskite components. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a schematic structural diagram of an expandable composite hole transport layer-based perovskite solar cell in Example 1 of the present invention;
[0032] Figure 2 The magnetron sputtering deposition of NiO in Examples 1, 3 and 4 of the present invention is X Schematic diagram of the film;
[0033] Figure 3is a schematic diagram of an immersion device for preparing a self-assembled monolayer by an immersion method in Examples 1 and 2 of the present invention;
[0034] Figure 4 is an electrochemical impedance spectroscopy (EIS) graph of the perovskite solar cell prepared in Examples 1-4 of the present invention;
[0035] Figure 5 It is a JV curve diagram of the optimal perovskite solar cell based on each hole transport layer prepared in Examples 1-4 of the present invention. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] A method for preparing an expandable composite hole transport layer-based perovskite solar cell comprises the following steps:
[0039] (1) In order to prevent the test fixture from piercing the film and causing a short circuit in the battery, part of the surface of the FTO conductive substrate is etched. The specific method is as follows:
[0040] Use a glass cutter to cut a long strip of FTO glass with a size of 15mm×200mm, then use 3M high-temperature polyimide tape to completely stick the 15×150mm area, and cover the exposed part with zinc powder. Use 2mol / L HCl to titrate the zinc powder covered area, and complete the FTO etching after the replacement reaction occurs. After the etching is completed, cut the long strip of FTO glass into 20×15mm one by one 2 The obtained small-sized FTO glass was subjected to ultrasonic treatment with detergent, acetone, and ethanol for 20 minutes each to remove surface impurities, and then 2 After removing the surface moisture with a gun, place it on a 120℃ heating table for drying.
[0041] (2) Deposition of dense NiO on the surface of FTO substrate X Hole transport layer, the specific method is:
[0042] The clean FTO substrate obtained in step (1) was placed in an ozone cleaning machine for 15 minutes, and the cleaned FTO substrate was placed in a magnetron sputtering device for the bottom NiO XDeposition of thin film. A metal nickel target and a DC sputtering power supply were used in the sputtering, with a power of 20W, a chamber pressure of 0.3Pa, an oxygen flow rate of 20sccm (standard cubic centimeters per minute), and an argon flow rate of 10sccm, so the volume ratio of oxygen to argon was 20:10. The coating time was 2min, and the film thickness was 10nm. After the sputtering was completed, the substrate was taken out of the magnetron sputtering device and annealed in air at 300℃ for 30min.
[0043] (3) MeO-2PACz and 4PACz were added to ethanol at a mass ratio of 1:1 to prepare a monolayer solution with a total concentration of MeO-2PACz and 4PACz of 0.03 mg / mL. The annealed and cooled substrate was placed in an immersion device, and the monolayer solution was poured into the device until the substrate was submerged, and the substrate was immersed at room temperature for 10 hours. After the immersion, the substrate was removed from the immersion device and annealed in air at 100°C for 10 minutes.
[0044] (4) placing the annealed and cooled substrate in an immersion device, pouring anhydrous ethanol into the device until the substrate is submerged, and soaking for 30 seconds. After the soaking is completed, the substrate is taken out of the immersion device and annealed in air at 100° C. for 3 minutes to form an expandable composite hole transport layer (SAM).
[0045] (5) Preparation of MA on the surface of scalable composite hole transport layer 0.85 FA 0.15 PbI 3 Thin films as light absorbing layers:
[0046] 182.3 mg of MAI (methylamine iodide), 34.8 mg of FAI (formamidine iodide) and 622.3 mg of PbI 2 (Lead iodide) was added to 1 mL of a mixture of DMF and DMSO in a volume ratio of 4:1, and 1.35 mol / L MA was prepared. 0.85 FA 0.15 PbI 3 The precursor solution was stirred at 70 °C for 2 h until completely dissolved, and filtered through a 0.22 μm PTFE filter to obtain a clear and transparent orange-yellow solution as MA 0.85 FA 0.15 PbI 3 Perovskite precursor solution. Take 2 drops of the obtained precursor solution and add them to the substrate obtained in step (4). Adjust the parameters of the spin coater to 1000 rpm for 10 seconds and 4000 rpm for 30 seconds. Use ethyl acetate as the anti-solvent during the spin coating process. After spin coating, remove the substrate and anneal it on a heating table at 120°C for 15 minutes to obtain MA. 0.85 FA 0.15 PbI 3 Light absorbing layer.
[0047] (6) Preparation of C60 electron transport layer and BCP secondary electron transport layer:
[0048] After the perovskite light absorption layer is formed, the sample is placed in a vacuum coating machine, and C60 and BCP powders are placed in an alumina crucible respectively. -4 Under a pressure of 1.3 Pa, C60 with a thickness of 25 nm and BCP with a thickness of 3 nm were sequentially evaporated at a speed of 0.1 A° / s to obtain an electron transport layer.
[0049] (7) Electrode preparation:
[0050] After the electron transport layer is formed, the sample is placed in a vacuum coating machine, pure Ag particles are placed in a tungsten boat, and the sample is placed in a vacuum coating machine. -4 Under a pressure of 1.3 Pa, a 100nm thick Ag back electrode was evaporated at a rate of 1A° / s to complete the preparation of the perovskite solar cell.
[0051] Example 2
[0052] Same as Example 1, except that step (2) is removed.
[0053] Example 3
[0054] Same as Example 1, except that step (3) is removed.
[0055] Example 4
[0056] The same as Example 1, except that the self-assembled monolayer deposition by immersion method in step (3) is replaced by spin coating method, and the specific method is as follows: MeO-2PACz and 4PACz are added to ethanol at a mass ratio of 1:1 to prepare a monolayer solution with a total concentration of MeO-2PACz and 4PACz of 0.5 mg / mL. The annealed substrate is placed in a homogenizer and spin coated at a low speed of 1000 rpm for 3s and a high speed of 4000 rpm for 30s. After the spin coating is completed, the substrate is annealed at 100°C in air for 10 minutes.
[0057] The schematic diagram of the structure of the perovskite solar cell based on the composite hole transport layer prepared in Example 1 is as follows Figure 1 As shown, this type of perovskite solar cell is composed of FTO, NiO X , SAM, MA x FA 1-x PbI 3 , C60, BCP and Ag.
[0058] Figure 2 For preparing NiO in Examples 1, 3, and 4 XMagnetron sputtering image of the film. The FTO substrate is placed in the magnetron chamber. When the sputtering pressure is reached, Ar / O is introduced into the chamber. 2 Mixed gas. By applying a DC voltage between the cathode (target material) and the anode (coating chamber wall), a glow discharge is induced, argon gas is ionized to produce argon ions and electrons, which are accelerated to bombard the target material under the action of the electric field, causing the target material to be sputtered.
[0059] Figure 3 This is a schematic diagram of the immersion device for preparing the self-assembled monolayer by immersion method in Examples 1 and 2. X The film substrate is placed in a sealed container, a single molecule self-assembly solution is continuously injected into the sealed container, and the sealed container is sealed and left to stand.
[0060] The electrochemical impedance spectroscopy (EIS) test was performed on the perovskite solar cells prepared in Examples 1-4. The results are as follows: Figure 4 As shown, it can be seen that the scalable composite hole transport layer-based perovskite solar cell prepared in Example 1 exhibits the smallest series resistance and the largest composite resistance, which means that more holes are effectively collected and transferred inside the device, which is beneficial to improving the performance of PSCs.
[0061] Figure 5 The JV curves of photovoltaic devices obtained in different embodiments under standard test conditions (AM1.5G illumination) are as follows: energy conversion efficiency 20.03%, open circuit voltage 1.02V, short circuit current 23.47mA / cm 2 , the filling factor is 83.36%. The performance parameters of the perovskite battery device prepared in Example 2 are: energy conversion efficiency 18.72%, open circuit voltage 0.99V, short circuit current 23.51mA / cm 2 , the filling factor is 80.74%. The performance parameters of the perovskite battery device prepared in Example 3 are as follows: energy conversion efficiency is 18.84%, open circuit voltage is 0.97V, short circuit current is 23.51mA / cm 2 , the filling factor is 82.55%. The performance parameters of the perovskite battery device prepared in Example 4 are as follows: energy conversion efficiency is 19.39%, open circuit voltage is 1.01V, short circuit current is 23.27mA / cm 2 , the filling factor is 81.89%. From the above data, it can be seen that the performance of the device using the expandable composite hole transport layer is significantly improved compared with the single hole transport layer.
[0062] The above is only an exemplary embodiment of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principles of the present invention, and these improvements and modifications should also be considered as the protection scope of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention shall be implemented according to the conventional means in the art unless otherwise specified and limited.
Claims
1. A scalable composite hole transport layer for perovskite solar cells, characterized in that: The expandable composite hole transport layer is composed of a bottom nickel oxide film and a top self-assembled monolayer.
2. The scalable composite hole transport layer according to claim 1, characterized in that: The thickness of the bottom nickel oxide film is 5-30nm.
3. The scalable composite hole transport layer according to claim 1, characterized in that: The monomolecular material of the top self-assembled monolayer is one or more of 2-(3,6-dimethyl-9H-carbazole-9-yl)ethyl)phosphonic acid, (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid, (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid, (2-(9H-carbazole-9-yl)ethyl)phosphonic acid, (4-(9H-carbazole-9-yl)butyl)phosphonic acid, (4-(7H-dibenzocarbazole-7-yl)butyl)phosphonic acid, (4-(2,7-dibromo-9,9-dimethylacridine-10(9H)-yl)butyl)phosphonic acid, (2-(3,6-dibromo-9H-carbazole-9-yl)ethyl)phosphonic acid and (4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl)phosphonic acid.
4. A method for preparing an expandable composite hole transport layer according to any one of claims 1 to 3, characterized in that: The steps include: (1) using a metal nickel target or a ceramic nickel oxide target to sputter and deposit an underlying nickel oxide film; (2) annealing the nickel oxide film; (3) depositing a top self-assembled monolayer on the nickel oxide film by an immersion method; (4) annealing the self-assembled monolayer; (5) cleaning the top self-assembled monolayer by immersion method; (6) Annealing the cleaned top self-assembled monolayer to obtain the expandable composite hole transport layer.
5. The preparation method according to claim 4, characterized in that: In step (1), the purity of the metal nickel target or the ceramic nickel oxide target is not less than 95%, the sputtering is magnetron sputtering, the sputtering power is 20W-120W, the gas pressure is 0.1Pa-10Pa, and the volume ratio of chamber oxygen and argon is 1-20:0-1.
6. The preparation method according to claim 4, characterized in that: In step (2), the annealing treatment is carried out in an air environment, the annealing temperature is 25-500° C., and the annealing time is 1-60 min.
7. The preparation method according to claim 4, characterized in that: In step (3), the immersion method is to add the monomolecular material to a solvent to prepare a monomolecular layer solution with a concentration of 0.02-0.05 mg / mL, and then immerse the sample in the monomolecular layer solution for 1-12 hours at a solution temperature of -40°C.
8. The preparation method according to claim 4, characterized in that: In step (4), the annealing treatment is carried out in an air environment, the annealing temperature is 80-120° C., and the annealing time is 10-20 min.
9. The preparation method according to claim 4, characterized in that: In step (5), the cleaning solution used for cleaning is one or more of ethanol, isopropanol and deionized water, and the immersion time of the cleaning solution is 0-120s.
10. The preparation method according to claim 4, characterized in that: In step (6), the annealing treatment is carried out in an air environment, the annealing temperature is 80-120° C., and the annealing time is 3-5 min.
11. A scalable composite hole transport layer-based perovskite solar cell, characterized in that: The hole transport layer of the perovskite solar cell is an expandable composite hole transport layer according to any one of claims 1 to 3.
12. The scalable composite hole transport layer-based perovskite solar cell according to claim 11, characterized in that: It includes a transparent substrate; a transparent conductive layer is formed on the transparent substrate; the expandable composite hole transport layer is formed on the transparent conductive layer; a perovskite layer is formed on the expandable composite hole transport layer; an electron transport layer is formed on the perovskite layer; and a back electrode is formed on the electron transport layer.
13. The scalable composite hole transport layer-based perovskite solar cell according to claim 12, characterized in that: The transparent conductive layer is selected from one or more of indium tin oxide, fluorine-doped tin dioxide and indium-doped zinc oxide; the component of the perovskite layer is MA x FA 1-x PbI3; the electron transport layer is selected from one or more of (6,6)-phenyl-C61-butylene isomethyl ester, C60, 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline; the back electrode is selected from one or more of ITO, AZO, IWO, Au, Ag, Cu, Al, Ni, Cr, and Pt; the transparent substrate is glass.
Citation Information
Cited By
Composite hole transport layer, preparation method and application thereof, perovskite cell and preparation method thereof
CN120730918A
Perovskite cell and preparation method thereof, laminated cell and photovoltaic module
CN120813168A